2018
DOI: 10.11594/jtls.08.01.10
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Effect of Pterocarpus indicus Willd Leaves Extract Against Replication of Dengue Virus (DENV) In Vitro

Abstract: Dengue hemorrhagic fever (DHF) is major public health problem in tropical and subtropical areas of the world with lack of approved vaccines and effective antiviral therapies. With no current treatment for illness attributed to dengue virus (DENV) infection other than supportive care, therapeutic strategies that use natural extract was developed.Indonesia have many plants that potential for antiviral drµgs such as Pterocarpus indicus Willd (P. indicus). The objective of this study was to determine the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The previous study showed that methanolic leaf extracts of Hippophae rhamnoides , sea-buckthorn from a family of Elaegnaceae is a potential candidate for dengue infection management [15]. Other herbal medicines such as S. baicalensis extract showed inhibition of DENV serotypes replication in vitro by reducing DENV infectivity and replication in Vero cells [16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The previous study showed that methanolic leaf extracts of Hippophae rhamnoides , sea-buckthorn from a family of Elaegnaceae is a potential candidate for dengue infection management [15]. Other herbal medicines such as S. baicalensis extract showed inhibition of DENV serotypes replication in vitro by reducing DENV infectivity and replication in Vero cells [16].…”
Section: Discussionmentioning
confidence: 99%
“…Propagation of DENV and antiviral assay in this study was done the same way as in the previous study with slight modification [16]. We used 96 well-plat flat bottom well plate for cytotoxicity and antiviral assays.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations